ANALYSIS OF CRIMINAL DISPARITY FOR NARCOTICS CRIMINAL ACTIONS - adminjfh, adminjfh (Fakultas Hukum Universitas Selamat Sri, 2022)
Disparity in criminal decisions has the meaning of unequal punishment of convicts in the same case orcases with approximately the same level of crime, whether carried out simultaneously or withoutjustification. This study aims to determine and analyze the basic considerations of judges in makingcriminal decisions against drug offenders. Identify the factors that influence the judge's decision againstthe perpetrators, especially those who violate Article 111 and Article 114 Paragraph 1 of Law Number35 of 2009 concerning Drugs. The data used is secondary data in the form of a judge's decision. Theanalytical approach used is the case approach and the concept of criminal law. The results of this studyindicate that in deciding cases, judges use the consideration of evidence as regulated in the CriminalProcedure Code. There are three factors that cause the judge's decision, namely: the legal factor itself,the perpetrator factor and the judge concerned.